2013
DOI: 10.1088/0031-9155/58/5/1315
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of VMAT dosimetric verifications between fixed and rotating gantry positions

Abstract: This study comparatively analysed dose distributions between the fixed and rotating gantry positions of volumetric-modulated arc therapy (VMAT) plans measured using different dosimetric techniques with the intent to provide pre-treatment quality assurance (QA). A total of 12 VMAT plans for the treatment of anatomical sites of various complexities were chosen. An ion chamber was used to measure the absolute central point doses, while EPID, Seven29, Matrixx and Delta4 were used to measure the dose distributions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Several groups have investigated the applicability of pre treatment verification of the IMRT and VMAT techniques with MatriXX and EPID. Zhu et al [10] compared the gamma pass rates of the VMAT QA using EPID and MatriXX and reported that the gamma pass rates were greater than 98% when the 3%/3 mm gamma criterion and a threshold of 10% were applied. They also noted a reduction in gamma pass rates when the 2%/2 mm criterion was employed for variable gantry positions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several groups have investigated the applicability of pre treatment verification of the IMRT and VMAT techniques with MatriXX and EPID. Zhu et al [10] compared the gamma pass rates of the VMAT QA using EPID and MatriXX and reported that the gamma pass rates were greater than 98% when the 3%/3 mm gamma criterion and a threshold of 10% were applied. They also noted a reduction in gamma pass rates when the 2%/2 mm criterion was employed for variable gantry positions.…”
Section: Discussionmentioning
confidence: 99%
“…The diode-detector-based MapCHECK (Sun Nuclear Corporation, US) [7], the ion-chamber based Seven29 2D array (PTW, Germany) [8,9], and MatriXX (IBA Dosimetry, Germany) [10][11][12][13][14] are commonly used commercial 2D detector arrays. The MatriXX array has a linear response with dose and it is independent of energy [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…53 This method uses both dose difference and distance to agreement criteria to evaluate the difference between planned and measured doses on a point-by-point basis. [56][57][58][59] If using the standard gamma index method many institutions use a 3%/3 mm criterion or even 5%/5 mm; however, it has been shown that this may not detect significant errors. Dose difference is used for the low gradient areas, and distance to agreement is used in high gradient areas.…”
Section: Patient-specific Qamentioning
confidence: 99%